Ways of Developing the Field of Services in the Digital Economy - Shavkatovna, Komilova Mukammal; Shuxratovna, Mirzaxadjayeva Shaxzoda (Research Parks Publishers, 2023)
the article focuses on the development of the service sector, its importance today. Also, the specific aspects, theoretical and practical issues of the development of the service sector today are highlighted.